(3TQM RGjQLI eaJGM GdcfhRs - (3Sgd Hf YHO Gddgs; (3GhMO GdOjf YHO Gddg Hf eSYhO GdMSjfj, GdHdjGfj,J (B686 (3g` s ((3HQGb aVjd GdNRQLj s)
(3ChdgG (B:s
(3hHYO agPg RGjQLI eaGJjM GdcfhR GdJj JfHF Yf LejY GdWdHGJ s
(3BNQgG (B:s
(3hfMf fQLh YOe GdJWhjd Nha ef GdedGdI Je GdcJGH hGdMeO ddg ChdkG BNQkG s
(3GdfSNI HgG MhGTs
(3eaJGM GdcfhR ai GdQed GfXQ cTa GdXfhf L (B2 (3U` (B1770s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1770s
Keywords: (3GdMQha h GdChaGbs